Notes on a Medieaval Burgess's House at Inverkeithing (Proceedings of the Society of Antiquaries of Scotland, 1913)
Fordell House is of fifteenth century date and follows the design of the small " keep," both in arrangement of parts and in details of workmanship. Houses of this type and date only rarely survive in Scotland. Detailed plans and elevations are included.